Odpowiedź:
6.3
1/x²
założenie:
x² ≠ 0
x ≠ 0
D: x ∈ R \ {0}
b)
3x + 7)/(2x(x - 2)(x + 3)
założenie:
2x(x - 2)(x + 3) ≠ 0
2x ≠ 0 ∧ x - 2 ≠ 0 ∧ x + 3 ≠ 0
x ≠ 0 ∧ x ≠ 2 ∧ x ≠ - 3
D: x ∈ R \ { - 3 , 0 , 2 }
1/(x⁴ - 16)
założenie:
x⁴ - 16 ≠ 0
(x² - 4)(x² + 4) ≠ 0
Ponieważ x² + 4 > 0 dla x ∈ R więc:
x² - 4 ≠ 0
(x - 2)(x + 2) ≠ 0
x - 2 ≠ 0 ∧ x + 2 ≠ 0
x ≠ 2 ∧ x ≠ - 2
D: x ∈ R \ { - 2 , 2 }
d)
(x² - 4x + 5)/(x³ + 3x² + 3x + 1)
założenie:
x³ + 3x² + 3x + 1 ≠ 0
(x² + 2x + 1)(x + 1) ≠ 0
(x + 1)² * (x + 1) ≠ 0
x + 1 ≠ 0
x ≠ - 1
D: x ∈ R \ {- 1}